Distributed Monitoring and Controlling Using Microcontroller and Virtual Internet Protocol - Ahmad Ashari (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
Nowadays, the applications based on TCP/IP (transmission control protocol/internet protocol) network are growing rapidly. By this application monitoring and control functions are easily and widely accessible through networks. Every PC (Personal Computer) can be connected to several microcontroller, but there are difficulties to access microcontroller directly through TCP/IP networks. This research study the use of virtual IP on a PC that connected with several microcontrollers, where each microcontroller is connected to a sensor device to monitoring temperature and a relay for controlling. In this method, each set of the microcontroller can be accessed directly using the IP. The results show that this system can be a distributed monitoring and controlling system which has the ability to record and display the results in the form of graphs.